2021
DOI: 10.18502/jri.v22i2.5796
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Resistance Index of Testicular Artery Using Color Doppler Ultrasound in Infertile Men Undergoing Varicocelectomy

Abstract: Background: Varicocele is one of the leading causes of infertility in men. Resistance index (RI) in testis is a parameter indicating parenchymal perfusion and microvascular functions. Increased RI in the testis of patients with varicocele might be a sign of impairments in microvascularization and a significant decrease in testicular perfusion. In the present study, RI in capsular and intraparenchymal testicular arteries was evaluated in patients with varicocele who underwent varicocelectomy. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, an increase in wash-in rate was also observed in the controls without varicocele and oligospermia, showing the efficacy of this specific DCE-MRI parameter to detect minor changes of testicular microcirculation in men with defective spermatogenesis (18). CDUS also assessed the hemodynamic changes and the testicular vascularization in testes with clinical varicocele (11)(12)(13)(14)(15)(16). A significant decrease in testicular arterial blood flow was noted, manifested as an increase in peak systolic velocity and resistive index in testes with clinical varicocele (11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In addition, an increase in wash-in rate was also observed in the controls without varicocele and oligospermia, showing the efficacy of this specific DCE-MRI parameter to detect minor changes of testicular microcirculation in men with defective spermatogenesis (18). CDUS also assessed the hemodynamic changes and the testicular vascularization in testes with clinical varicocele (11)(12)(13)(14)(15)(16). A significant decrease in testicular arterial blood flow was noted, manifested as an increase in peak systolic velocity and resistive index in testes with clinical varicocele (11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 79%
“…The study of alterations of testicular perfusion in infertile men with varicocele represents a topic of active research (1,1118). Similar to our results, CEUS in a study of 90 men with left varicocele, found higher values of wash-in rate in patients with varicocele associated with either normozoospermia or oligospermia (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations